The karaite interpretation of the plural forms in Genesis 1.26, 3.5 and 3.22 compared to their classical rabbinic exposition - Oseka, Matthew (Vox Scripturae - Revista Teológica Internacional, 2025)
The present paper examines the history of the Karaite interpretation of the plural forms in Genesis 1.26, 3.5 and 3.22 pertinent to the Divine, situating it against the Rabbinic tradition. Furthermore, the present essay analyses how Karaite exegetes substantiated their views without recognising the authority of the Rabbinic texts such as Targumim, Midrashim or the Babylonian Talmud which elucidated such phenomena in the Tanakh. The study of the Karaite exegesis relies on the complete commentaries on the Pentateuch penned by Aaron ben Joseph and by Aaron ben Elijah.